The Effect of Financial Reporting Quality, Corporate Governance, and Asset Management on Financial Distress in The Syariah Savings, Loans and Financing Cooperative Syirkah Fastabiqul Khoirot Lumajang - Saadatu Mukarromatil Arifah; Adynda Cindy Savinah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2026)
This study aims to empirically examine the influence of financial reporting quality, corporate governance, and asset management on financial distress at the Syirkah Fastabiqul Khoirot Lumajang Sharia Savings and Loans Cooperative (KSPPS). Using a quantitative method with a causality approach, the research data were sourced from monthly financial reports and annual sharia supervision reports. Data analysis was performed using multiple linear regression techniques after meeting the classical assumption test. The results indicate that transparent financial reporting quality and sharia-based corporate governance have a significant negative effect on reducing the risk of financial distress. Similarly, diligent asset management through controlling the non-performing financing ratio significantly maintains the cooperative's liquidity stability from the threat of financial distress. The implementation of trustworthy governance and the preparation of accountable financial reporting are key to maintaining the operational sustainability of sharia microfinance institutions.